Decreased circulating T regulatory lymphocytes in obese patients undergoing bariatric surgery. - Claudia Agabiti-Rosei; Valentina Trapletti; Silvia Piantoni; Paolo Airò; Angela Tincani; Carolina De Ciuceis; Claudia Rossini; Francesco Mittempergher; Amin Titi; Nazario Portolani; Stefano Caletti; Maria Antonietta Coschignano; et al. (PLoS ONE, 2018)
It has been previously demonstrated that T lymphocytes may be involved in the development of hypertension and microvascular remodeling, and that circulating T effector lymphocytes may be increased in hypertension. In particular, Th1 and Th 17 lymphocytes may contribute to the progression of hypertension and microvascular damage while T-regulatory (Treg) lymphocytes seem to be protective in this regard. However, no data is available about patients with severe obesity, in which pronounced microvascular alterations were observed.We have investigated 32 severely obese patients undergoing bariatric surgery, as well as 24 normotensive lean subjects and 12 hypertensive lean subjects undergoing an elective surgical intervention. A peripheral blood sample was obtained before surgery for assessment of CD4+ T lymphocyte subpopulations. Lymphocyte phenotype was evaluated by flow cytometry in order to assess T-effector and Treg lymphocytes.A marked reduction of several Treg subpopulations was observed in obese patients compared with controls, together with an increased in CD4+ effector memory T-effector cells.In severely obese patients, Treg lymphocytes are clearly reduced and CD4+ effector memory cells are increased. It may be hypothesized that they might contribute to the development of marked microvascular alterations previously observed in these patients.